115k views
1 vote
Find the partial derivative of the function f(x,y)=Integral of cos(-7t^2-6t-1)dt. Find fx(x,y) and fy(x,y)

User Rowmoin
by
5.2k points

1 Answer

3 votes

Answer:


\mathbf{(\partial f)/(\partial x)= cos (-7x^2 -6x - 1)}


\mathbf{(\partial f)/(\partial y)= cos ( -7y^2 -6y-1)}

Explanation:

Given that :


f(x,y) = \int ^x_y cos (-7t^2 -6t-1) dt

Using the Leibnitz rule of differentiation,


(d)/(dt) \int ^(b(t))_(a(t)) f(x,t) dt= f(b(t),t) *b'(t) -f(a(t),t) * a' (t) + \int^(b(t))_(a(t)) (\partial f)/(\partial t) \ dt

To find: fx(x,y)


(\partial f)/(\partial x)= (\partial )/(\partial x) [ \int ^x_y cos (-7t^2 -6t -1 ) \ dt]


(\partial f)/(\partial x)= (\partial x)/(\partial x) cos (-7x^2 -6x -1 ) - (\partial y)/(\partial x) * cos (-7y^2 -6y-1) + \int ^x_y [(\partial )/(\partial x) \ \{cos (-7t^2-6t-1)\}] \ dt


(\partial f)/(\partial x)= cos (-7x^2 -6x - 1) -0+0


\mathbf{(\partial f)/(\partial x)= cos (-7x^2 -6x - 1)}

To find: fy(x,y)


(\partial f)/(\partial y)= (\partial )/(\partial y) [ \int ^x_y cos (-7t^2 -6t -1 ) \ dt]


(\partial f)/(\partial y)= (\partial x)/(\partial y) cos (-7x^2 -6x -1 ) - (\partial y)/(\partial y) * cos (-7y^2 -6y-1) + \int ^x_y [(\partial )/(\partial y) \ \{cos (-7t^2-6t-1)\}] \ dt


(\partial f)/(\partial y)= 0 - cos ( -7y^2 -6y-1)+0


\mathbf{(\partial f)/(\partial y)= cos ( -7y^2 -6y-1)}

User Ahmed Fasih
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.